(untitled) (Economic studies journal, 2021)
Abstract Throughout the ages, humanity has faced many pandemics and chronic diseases that cost lives and caused major crises with long-lasting effects and consequences. Today, the world is going through a state of confusion and instability at all levels. It is under pressure of a global pandemic with repercussions on, and underlying challenges in, various areas of life. Furthermore, our era was marked by the Fourth Industrial Revolution, which mainly driven by technology. In fact, technology is being extensively used in all areas of life, as institutions and individuals increasingly relied heavily on it in performing their daily work, especially in the aftermath of the covid-19 pandemic. As most countries closed their borders and isolated themselves from the rest of the world to deal with the pandemic and prevent its spread, business experienced disruptions and, in some cases, were completely paralyzed, causing severe damage to the economic activity in both developed and developing countries alike. Although the cause is the same, the consequences were not limited to the above but expanded also to other areas, such as, health complications, and social and psychological problems. In addition, there was a global economic recession that resulted in closure of businesses and their exit from the market; an increased unemployed; inability to pay; and financial confusion in the local and global markets. Hence, it appears that a country’s technological capacity development will be one of the key factors to bet on in the future to deal with, and to curb, this pandemic in any country. Libya, as a part of the global approach, is not an exception. This fact poses a real challenge for the business sector, which will inevitability need to adapt to the new realities. One way to do so is to reconsider its management methods by adopting those methods that rely on modern technology, not only in the hardware- such as technical equipments- but also in organization, management, and the exercise of the leadership process in various organizational aspects. The technology, before being a machine or a device, is an idea born of a need - as demonstrated by the Covid- 19 pandemic - or an interest. Thus, its adoption should be part of a comprehensive framework that covers all aspects of work. Thus, this paper aims to shed light on the environment of the Libyan business sector and to describe the extent to which it employs technology in its business activities and extent of the impact to the Covid-19. A set of recommendations will be presented that will enhance the optimal use of technology in this vital sector in Libya.